Eksplorasi Validitas dan Reliabilitas Soal Pemahaman Konsep Dalam Asesmen Pembelajaran - Amelia, Nurul; Erita, Selvia (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Students’ understanding of concept can be measured and assessed using mathematical concept understanding test instruments. The instrument to be used must be prepared to meet the criteria for a good instrument. Therefore, the aim of this research is to determine the validity and reliability of students' conceptual understanding questions in learning assessments. This type of research is qualitative research using descriptive methods. Data was obtained through tests and interviews with mathematics subject teachers. The subjects in this research were class IX students at MTsN 2 Kerinci, totaling 22 students in 1 class. Based on the results of validity calculations using the Pearson Product Moment formula and t test, as well as calculations of question reliability using the Cronbach's Alpha formula, it was found that each question item was valid and reliable, so this test instrument can be used to measure students' ability to understand mathematical concepts.